Pengaruh Sikap Kreatif dan Dukungan Orang Tua Terhadap Keberlanjutan Usaha - Widya Nuriyanti; Toto Widiarto (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to find the influence of creative attitudes on business sustainability, to find the influence of creative attitudes and support from parents on business sustainability. This study used qualitative research methods. The population was 112 students of SMK Yadika 5 Jakarta. The sample consisted of 31 students of class X 2017/2018 academic year. Interview, documentation and questionnaire techniques. The data analysis technique used the Autocorrelation Test, Multicollinearity Test. Multiple regression analysis is used in this research model. Using the SPSS 20 program. The results show that there is an influence of creative attitudes on business sustainability. There is an influence of parental support on business sustainability and there is an influence on creative attitudes and support from parents for business continuity. Suggestions in this study are that parents and teachers can provide learning more creative attitudes. The attention given by parents also influences the sustainability of new entrepreneurs pioneered by entrepreneurs.